Photoacoustic Mouse Brain Imaging Using an Optical Fabry-Pérot Interferometric Ultrasound Sensor - Chen, Yuwen; Chen, Buhua; Yu, Tengfei; Yin, Lu; Sun, Mingjian; He, Wen; Ma, Cheng (Frontiers in Neuroscience, 2021)
Photoacoustic (PA, or optoacoustic, OA) mesoscopy is a powerful tool for mouse cerebral imaging, which offers high resolution three-dimensional (3D) images with optical absorption contrast inside the optically turbid brain. The image quality of a PA mesoscope relies on the ultrasonic transducer which detects the PA signals. An all-optical ultrasound sensor based on a Fabry-Pérot (FP) polymer cavity has the following advantages: broadband frequency response, wide angular coverage and small footprint. Here, we present 3D PA mesoscopic imaging of the mouse brain using such an optical sensor. A heating laser was used to stabilize the sensor’s cavity length during the imaging process. To acquire data for a 3D angiogram of the mouse brain, the sensor was mounted on a translation stage and raster scanned. 3D images of the mouse brain vasculature were reconstructed which showed cerebrovascular structure up to a depth of 8 mm.